Answer:
y: (5, -5)
Step-by-step explanation:
Answer:
The option "StartFraction negative 2 (x + 6) Over (x + 4) (x minus 4) EndFraction" is correct
That is ![\frac{-2(x+6)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7B-2%28x%2B6%29%7D%7B%28x%2B4%29%28x-4%29%7D)
Therefore ![\frac{x}{x^2-16}-\frac{3}{x-4}=\frac{-2(x+6)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7Bx%5E2-16%7D-%5Cfrac%7B3%7D%7Bx-4%7D%3D%5Cfrac%7B-2%28x%2B6%29%7D%7B%28x%2B4%29%28x-4%29%7D)
Step-by-step explanation:
Given problem is StartFraction x Over x squared minus 16 EndFraction minus StartFraction 3 Over x minus 4 EndFraction
It can be written as below :
![\frac{x}{x^2-16}-\frac{3}{x-4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7Bx%5E2-16%7D-%5Cfrac%7B3%7D%7Bx-4%7D)
To solve the given expression
![\frac{x}{x^2-16}-\frac{3}{x-4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7Bx%5E2-16%7D-%5Cfrac%7B3%7D%7Bx-4%7D)
![=\frac{x}{x^2-4^2}-\frac{3}{x-4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bx%7D%7Bx%5E2-4%5E2%7D-%5Cfrac%7B3%7D%7Bx-4%7D)
( using the property
)
![=\frac{x-3(x+4)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bx-3%28x%2B4%29%7D%7B%28x%2B4%29%28x-4%29%7D)
( by using distributive property )
![=\frac{-2x-12}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-2x-12%7D%7B%28x%2B4%29%28x-4%29%7D)
![=\frac{-2(x+6)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-2%28x%2B6%29%7D%7B%28x%2B4%29%28x-4%29%7D)
![\frac{x}{x^2-16}-\frac{3}{x-4}=\frac{-2(x+6)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7Bx%5E2-16%7D-%5Cfrac%7B3%7D%7Bx-4%7D%3D%5Cfrac%7B-2%28x%2B6%29%7D%7B%28x%2B4%29%28x-4%29%7D)
Therefore ![\frac{x}{x^2-16}-\frac{3}{x-4}=\frac{-2(x+6)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7Bx%5E2-16%7D-%5Cfrac%7B3%7D%7Bx-4%7D%3D%5Cfrac%7B-2%28x%2B6%29%7D%7B%28x%2B4%29%28x-4%29%7D)
Therefore the option "StartFraction negative 2 (x + 6) Over (x + 4) (x minus 4) EndFraction" is correct
That is ![\frac{-2(x+6)}{(x+4)(x-4)}](https://tex.z-dn.net/?f=%5Cfrac%7B-2%28x%2B6%29%7D%7B%28x%2B4%29%28x-4%29%7D)
Step-by-step explanation:
Please refer to the attachment
Kinetic Energy
=
1
2
m
v
2
=
1
2
1120
⋅
40
2
=
896000
J
=
8.96
⋅
10
5
J